2010
DOI: 10.3233/jad-2010-091669
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Cognitive Impairment: Current Epidemiology and Possible Underlying Mechanisms

Abstract: A possible role of vascular and lifestyle-related factors was recently proposed for age-related changes of cognitive function, predementia syndromes, and cognitive decline of degenerative (Alzheimer's disease, AD) or vascular origin (vascular dementia, VaD). At present, cumulative evidence suggests that vascular risk factors may be important in the development of mild cognitive impairment (MCI), dementia, and AD. Among vascular-related factors, metabolic syndrome (MetS) has been associated with the risk of cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 224 publications
4
103
2
2
Order By: Relevance
“…This is particularly relevant for MCI which is recognized to be a pathology-based condition with a high rate of progression to AD (Petersen et al 1999), and thus, the BBB may have already been compromised in our MCI patients. The inclusion in the analyses of untreated hypertensives was important to identify the risk contribution of hypertension to incident MCI (Panza et al 2010). The exclusion of this sub-sample would have reduced the risk of incident MCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly relevant for MCI which is recognized to be a pathology-based condition with a high rate of progression to AD (Petersen et al 1999), and thus, the BBB may have already been compromised in our MCI patients. The inclusion in the analyses of untreated hypertensives was important to identify the risk contribution of hypertension to incident MCI (Panza et al 2010). The exclusion of this sub-sample would have reduced the risk of incident MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Both longitudinal and cross-sectional studies suggested that elevated midlife blood pressure or hypertension contribute to the development of Alzheimer's disease (AD) and overall dementia, although this effect is weaker in the years preceding dementia onset (Panza et al 2010). In particular, hypertension at baseline was related to greater cognitive decline or mild cognitive impairment (MCI) (Panza et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, both dose reduction and guided discontinuation of SGAs were shown to lead to cognitive improvement in stable patients (Faber et al 2012;Takeuchi et al 2013). Several factors associated with cognitive dysfunction in healthy subjects, such as metabolic syndrome, chronic substance use and stress (Johnsen & Asbjørnsen, 2008;Panza et al 2010;Stavro et al 2013), are more common in schizophrenia and there is no doubt that they can contribute to cognitive impairment in schizophrenia. For example, some studies have shown that schizophrenia patients who have co-morbid metabolic syndrome, diabetes mellitus, hypertension, obesity, post-traumatic stress disorder (PTSD) and alcohol use disorder have more cognitive impairment than other patients without such comorbidities (Goodman et al 2007;Dickinson et al 2008;Fan et al 2008;Manning et al 2009;Friedman et al 2010;Lindenmayer et al 2012;Takayanagi et al 2012;Guo et al 2013).…”
Section: Neurodevelopment and Medical Co-morbidities Substance Use Amentioning
confidence: 99%
“…Vascular factors such as arterial hypertension, dyslipidemia, hyperinsulinemia and DM2, obesity, subclinical atherosclerosis and arrhythmias have been associated with high risks of cognitive impairment and dementia (52). Studies in Latin America have also shown that metabolic syndrome doubles the risk of cognitive impairment (57). Kalaria (58) has indicated that the gradual adoption of westernized lifestyle involving excessive caloric intake, unhealthy diet, and decreased physical activity, favors the appearance of conditions such as AD.…”
Section: Discussionmentioning
confidence: 99%